Paleozoic Fossils of Antonio Raimondi collection preserved at the Museum of Natural History - National University of San Marcos, Lima-Peru, 1st part - Prado Velazco, Ysabel (2012)
The present work aims to make known the valuable palaeontological collections preserves the Geosciences Division Museum, among which is the collection Antonio Raimondi and form part of the Network of Automated Collections of the Museums of the world. This publication is the first part of the project: "Books and Automated Update of Minerals, Rocks and Fossils Antonio Raimondi Collection" at the Museum of Natural History, which was developed during the years 2009 to 2011 under the auspices of the National Research Council University San Marcos. Paleozoic fossils collected by Raimondi were studied by Gabb (1877), who identified three new species: Terebratula titicacensis, Productus papilio and Productus reticulatus. The author identifies and updates the following fossils: Paraconularia ulrichi, Reticonularia baini, African Paraconularia; Devonian Phacopina, Metacryphaeus giganteus, Metacryphaeus tuberculatus, Eldredgeia venustus; Australocoelia tourteloti, antisiensis Clarkeia, Australospirifer antarcticus, Dictyoclostus boliviensis, Cancrinella villiersi; Fusulina cylindrica; Fenestella flexuosa . Most of this paleofuana comes from Puno, is made up of benthic invertebrate fossils of shallow marine facies, is part of the province Malvinocáfrica and are of great stratigraphic value, for dating Periods Devonian, Pennsylvanian and Permian, corresponding to the Cabanillas Formation Groups and Excelsior, Tarma and Copacabana.